In vitro Antioxidant Potential and Cytotoxicity Study of Asparagus aethiopicus L. Extracts on HT-29 Human Colon Cancer Cell Line - Awati, Suhas Suresh; Gilhotra, Ritu M; Singh, Santosh K; Raj, Vinit; Wadkar, Kiran A (Indian Journal of Pharmaceutical Education and Research, 2020)
Objectives: To decide the phytochemical constituents, antioxidant and anticancer potential of Asparagus aethiopicus L. extracts on HT-29 human colon malignant growth cell line. Methods: The roots of plant were exposed to Hot Soxhlet continuous extraction with expanding polarity of solvents viz., pet ether, chloroform, ethanol and aqueous maceration. Qualitative phytochemical screening was completed by utilizing distinctive phytochemical tests. The antioxidant potential was tried utilizing 2, 2-diphenyl-1- picrylhydrazyl, ferric ion reducing power assay and phosphomolybdenum assay. In vitro anticancer action tried on HT-29 human colon malignant growth cell line and it was assessed by (3-(4, 5-dimethyl thiazole-2yl)- 2, 5-diphenyl tetrazolium bromide) MTT test. Results and Discussion: Preliminary qualitative phytochemical screening affirmed the presence of phytoconstituents like alkaloids, flavonoids, glycosides, saponins, sterols, tannins and reducing sugar. Antioxidant potential was demonstrated most noteworthy in ethanol extracts dependent on the test performed. The ethanol extracts were seen as an antioxidant and specifically cytotoxic to HT-29 human colon malignant growth cell line. Conclusion: The outcomes show that Asparagus aethiopicus L. having a potential of antioxidant activity and anticancer action on HT-29 human colon cancer cell line. In any case, further examinations are expected to presume that the particular constituent liable for its antioxidant action and cancer prevention agent.
Keywords: Phytochemical; Antioxidant; Anticancer; Colon cancer; Asparagus; aethiopicus